Ethylene and hydrogen peroxide in the aerenchyma formation in maize tolerant to intermittent flooding - Pires, Marinês Ferreira; Castro, Evaristo Mauro de; Magalhães, Paulo Cesar; Silva Neta, Izabel Costa; Monteiro, Aline Gomes Dias Pinto (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the role of ethylene and hydrogen peroxide (H2O2) in the aerenchyma formation in genetic selection cycles of the maize cultivar BRS 4154, under flooding. Plants from cycles C1 and C18 were flooded for 7 days, with roots collected at 0 (control, no flooding), 1, and 7 days. The following were evaluated: gene expression of the enzymes ACC synthase (ACS), ACC oxidase (ACO), superoxide dismutase (SOD), and ascorbate peroxidase (APX); ethylene production and H2O2 content; enzymatic activity of ACO; and aerenchyma proportion in the cortex. There was no expression of ACS and ACO. ACO activity and ethylene production varied. SOD expression was higher in C1 plants and that of APX in C18 plants, with reduction at 7 days. H2O2 content did not differ between treatments. The proportion of aerenchyma increased with time, being higher in C18 plants and related to the aerenchyma formation rate. The flooding time and the tolerance level of the selection cycle influence ethylene production. The expression of APX indicates greater H2O2 production at the beginning of flooding.